The Cretaceous Period of Weather Similar to the Present One and Its Diverse “Conchostracan” Fauna - Gallego, Oscar Florencio (2019)
Cretaceous System is widely represented in South America from northeast Brazil to southern Patagonia Argentina. It is characterized by having been a relatively warm climate, with rainfall and marked seasonality which allowed the development of the “conchostracan” populations.